Rank, Sex, Drugs, and Crime - Benjamin Elsner; Ingo E. Isphording (Institute for the Study of Labor (IZA), 2015)
In this paper we show that a student's ordinal rank in a high school cohort is an important determinant of engaging in risky behaviors. Using longitudinal data from representative US high schools, and exploiting idiosyncratic variation in the cohort composition within a school, we find a strong negative effect of a student's rank on the likelihood of smoking, drinking, having unprotected sex, and engaging in physical fights. We further provide suggestive evidence that these results are driven by status concerns and differences in career expectations.
Keywords: I12; I14; I21; I24; 330; risky behavior; ability rank; peer effects; beliefs; expectations